The novel use of zwitterionic bacterial components and polysaccharides in immunotherapy of cancer and immunosuppressed cancer patients. - Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Abu Bakar, Fatimah (InTech, 2012)
The recognition of pathogenic antigens as foreign particles by adaptive immune cells induces T and B lymphocytes to start defensive humoral and cellular reaction. Latest research revealed that proteins and some lipids are the main molecules inducing protective T cell responses during microbial infections while polysaccharides which are important components of microbial pathogens and many vaccines were not regarded as important antigens. However, research regarding the role of the adaptive immune system by polysaccharides gained interest only recently. Traditionally, polysaccharides were considered to be T cell-independent antigens that did not directly activate T cells or induce protective immune responses, but chemically modified polysaccharides, namely zwitterionic polysaccharides (ZPSs) were recently found highly immunogenic. Therefore, in this chapter we will discuss the role of zwittrionized polysaccharides in immune reaction induction and their immunostimulatory effect in cancer patients. Several studies were conducted to use ZPSs to induce vigorous immune response and to establish immunostimulatory or immunomodulatroy effect which can be used in cancer immunotherapy. Bacterial ZPSs that are naturally zwitterionic or those that were artificially zwitterionized were recently identified as potent immune regulators. The immunomodulatory effect of ZPSs requires antigen processing and presentation by antigen presenting cells, the activation of CD4 T cells and subpopulations of CD8 T cells and the modulation of host cytokine responses.